2011
DOI: 10.4061/2011/832163
|View full text |Cite
|
Sign up to set email alerts
|

Leptin: A Correlated Peptide to Papillary Thyroid Carcinoma?

Abstract: Introduction. Leptin as an adipose-tissue-related peptide hormone contributes to the control of food intake, energy expenditure, and other activities such as cell proliferation. Therefore, association of leptin level with thyroid cancer has been suggested recently. Considering that thyroid cancer is the most common endocrine cancer, the aim of this study was evaluation of leptin levels in thyroid cancer. Materials and Methods. 83 patients with papillary thyroid cancer (35 males and 48 females) with 90 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
2
18
0
1
Order By: Relevance
“…The comparison between patients and controls revealed higher levels of leptin and ICAM‐1 in patients. Our findings are consistent with those of previous studies, which demonstrated significantly higher levels of leptin in patients with thyroid cancer relative to a control group and a significant drop in serum leptin levels after surgical resection of thyroid cancer 21, 22. It is interesting to note that high leptin levels reportedly portend an aggressive disease course in breast and prostate cancer,23‐27 and an altered leptin signaling network, in concert with the phosphatidylinositol 3‐kinase/protein kinase B (PI3K/Akt) signaling pathway, reportedly plays a role in thyroid cancer development 28, 29.…”
Section: Discussionsupporting
confidence: 93%
“…The comparison between patients and controls revealed higher levels of leptin and ICAM‐1 in patients. Our findings are consistent with those of previous studies, which demonstrated significantly higher levels of leptin in patients with thyroid cancer relative to a control group and a significant drop in serum leptin levels after surgical resection of thyroid cancer 21, 22. It is interesting to note that high leptin levels reportedly portend an aggressive disease course in breast and prostate cancer,23‐27 and an altered leptin signaling network, in concert with the phosphatidylinositol 3‐kinase/protein kinase B (PI3K/Akt) signaling pathway, reportedly plays a role in thyroid cancer development 28, 29.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, leptin levels decreased in patients 20 days after total thyroidectomy although remained significantly higher than the control group . Similarly, in an Iranian cross‐sectional study (BEL 3, GR C) of patients with PTC ( n = 83) vs. controls ( n = 90), serum leptin levels were higher in the former . Lack of adjustment for potential confounders and the relatively small number of subjects in these studies casts doubt about the reliability and/or generalizability of their results, which need to be confirmed or refuted by future studies.…”
Section: Obesity and Thyroid Cancer Risk: Potential Mediatorsmentioning
confidence: 92%
“…Some studies have described the presence of high leptin levels in patients with DTC (24). Cheng and cols.…”
Section: Case Reportmentioning
confidence: 99%